PENGARUH VARIASI ROTATION TIME TERHADAP NILAI DLP (DOSE LENGTH PRODUCT) DAN IMAGE NOISE PADA PESAWAT MSCT 128 SLICE (STUDI KASUS) - Asmaul Fauziyah; Amillia Kartika Sari; Soegardo Indra P; Anggraini Dwi Sensusiati; Pramono (JRI (Jurnal Radiografer Indonesia), 2018)
Background: The patient's dose and image noise illustrate the quality of the CT scan. DLP (Dose Lenght Product) is a dose description on a CT-Scan tool by providing a measure of the total amount of radiation exposure for a series of scans. While image noise is the difference / variation in pixel values contained in an image matrix. The use of rotation time in CT scan is the most likely to contribute to patient dose and image noise. Method: Toshiba Aquilion 128 MSCT aircraft and Acrilyc phantom were used as material in this study. The parameters on the CT-Scan tool used are the suitability test parameters, namely at kV 120, 400mA, slice thickness 2 mm, FOV 240. Rotation time variations on CT scan imaging that can be selected are in the range of values ​​of 0.35s, 0.375s, 0.4s , 0.45s, 0.5s, 0.6s, 0.75s, 1.0s while the other parameters are the same. From each rotation time value, the estimated dose value is the DLP value on the CT Scan monitor screen (Summary). Furthermore, the scanning results measure the noise value by measuring the ROI on the middle side of the area around a diameter of 2-3 cm2. The measurement results are recorded and entered into tables, graphs and tests with statistics, and test the effect (regression) as hypothesis testing with a significant value (α) <0.05. This research was conducted in the Radiology IRD unit of Dr. RSU. Soetomo. Results: Obtained DLP values ​​of 37.3 mGy.cm, 28.4 mGy.cm, 23.1 mGy.cm, 19.5 mGy.cm, 17.8 mGy.cm, 16 mGy.cm, 15.1 mGy.cm and 14.2 mGy.cm at rotation times of 1.0s, 0.75s, 0.6s, 0.5s, 0.45s, 0.4s, 0.375s, 0.35s. For the assessment of image noise the results are 5.6 HU, 5.5 HU, 5.3 HU, 5.1 HU, 4.8 HU, 4.5 HU, 4.1 HU and 3.4 HU at rotation time 0 , 35s, 0.375s, 0.4s, 0.45s, 0.5s, 0.6s, 0.75s, 0.5s, and 1s. From the above results obtained the value of DLP at the lowest radiation dose on the use of rotation time of 0.35 sec which is 14.2 mGy.cm and the largest at 1.0 sec is 37.3 mGy.cm, with a regression coefficient of 1,785 + 35,507 with a value of 0,000 so that the effect is very significant . In this case it shows that the contribution of rotation time effect on optimization of the estimated DLP value is 100%. Noise value at the variation of rotation time values ​​found that 0.35 s produces an optimum noise of 5.6 HU and 1.0 sec produces the smallest noise of 3.4 HU. This can be seen from the regression coefficient of 6,637 - 3,344 with a value (α) <0.05. In this case it shows that the contribution of rotation time to the image noise value is 97.8% while the remaining 2.2% is influenced by other variables contained in the model. Conclusion: The use of slower rotation time is still recommended to produce optimal image quality in certain cases, because the noise value is close to zero and is still within the limits of the normal noise value. Each increase in rotation time of one unit will increase the optimization value of the estimated DLP by 35.507, so that it can be said there is no significant difference even though the measurement looks very varied in value.